PENGARUH MODEL KOOPERATIF TIPE MAKE A MATCH TERHADAP KETERAMPILAN MENULIS PANTUN SISWA KELAS VII SMP NEGERI 2 PARIAMAN - Ramadhanti, Khadijah; R., Syahrul; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACT This research is aimed to describe the influence of cooperative model Make A Match type concerning pantun writing skills of student class VII SMP Negeri 2 Pariaman. The research method of this study is experiment method with quasi experiment. The result of this study is there was significant influence of cooperative model Make A Match type concerning pantun writing skills of student class VII SMP Negeri 2 Pariaman at significant level 95% with degrees of freedom (n1+n2)-2, namely ttable <tarithmetic (1,67<1,89). Ho was rejected and H1 was accepted because the results of the hypothesis test prove that value of ttable was smaller than tarithmetic. Kata Kunci: pengaruh, kooperatif, Make A Match, pantun